Acting Near and Far - Darren Tunstall (Pamiętnik Teatralny, 2025)
A key question for the success of a dramatic scene is where the actor’s attention is directed because this influences in turn the audience’s point of attention. The actor’s movement in space in a play is discussed in terms of the Construal Level Theory of Yacov and Liberman, in which events, including mental events like dreams and recollections, are construed by the mind in terms of near and far. An example is given of how near/far mode construal affected my rehearsal of a scene from a recent British play. It is further suggested that near/far mode construal applies not only to non-verbal behaviour such as proxemics but to speech itself. A core function of speech is referential displacement to enable prediction for action beyond the immediate present, an idea that may be linked to the Regret Prediction Theory of Frith and Metzinger. I suggest that near/far mode is exemplified in Stanislavski’s productions of the plays of Chekhov. To be a good psychologist is to be socially valued, it is proposed, and a skilful use of near/far mode distinctions in both movement and speech thus is seen as a reliable indicator of (an actor’s) intelligence.